Electrochemically enabled rhodium-catalyzed [4 + 2] annulations of arenes with alkynes. Issue 23 (28th October 2021) - Wang, Zi-Chen; Li, Rui-Tao; Ma, Qiang; Chen, Jia-Yi; Ni, Shao-Fei; Li, Ming; Wen, Li-Rong; Zhang, Lin-Bao
Abstract : Herein, electrochemically driven, Rh(iii )-catalyzed regioselective annulations of arenes with alkynes have been established. Abstract : Herein, electrochemically driven, Rh(iii )-catalyzed regioselective annulations of arenes with alkynes have been established. The strategy, combining the use of a rhodium catalyst with electricity, not only avoids the need for using a stoichiometric amount of external oxidant, but also ensures that the transformations proceed under mild and green conditions, which enable broad functional group compatibility with a variety of substrates, including drugs and pharmaceutical motifs. Moreover, the electrolysis reaction was made operationally simple by employing an undivided cell, and proceeds efficiently in aqueous solution in air.